2010
DOI: 10.1007/jhep08(2010)074
|View full text |Cite
|
Sign up to set email alerts
|

Non-perturbative improvement of quark mass renormalization in two-flavour lattice QCD

Abstract: We non-perturbatively determine the renormalization constant and the improvement coefficients relating the renormalized current and subtracted quark mass of (quenched) valence quarks propagating in a sea of O(a) improved two massless quarks. We employ the Schrödinger functional scheme and fix the physical extent of the box by working at a constant value of the renormalized coupling. Our calculation yields results which cover two regions of bare parameter space. One is the weak-coupling region suitable for volu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 41 publications
6
76
0
Order By: Relevance
“…This paper follows up our previous work [19] on the definition of a line of constant physics in N f = 2 lattice simulations. It allows us to non-perturbatively study the quark mass dependence of relativistic QCD meson observables in a finite box of extent L 1 ≈ 0.4 fm [20].…”
Section: Observablesmentioning
confidence: 83%
See 4 more Smart Citations
“…This paper follows up our previous work [19] on the definition of a line of constant physics in N f = 2 lattice simulations. It allows us to non-perturbatively study the quark mass dependence of relativistic QCD meson observables in a finite box of extent L 1 ≈ 0.4 fm [20].…”
Section: Observablesmentioning
confidence: 83%
“…Equivalently, we will assign to them the dimensionless mass parameter z = L 1 M h from now on, where M h ≡ M denotes some fixed value of the renormalization group invariant (RGI) heavy quark mass. In [19] we have already shown that in such a small box the lattice spacing can be chosen small enough so that all heavy quarks up to a certain value can be simulated relativistically while keeping cutoff effects in the O(a) improved theory well under control. For any unexplained notation, the reader may consult [15,19].…”
Section: Observablesmentioning
confidence: 99%
See 3 more Smart Citations